EFFECT OF DAIDZEIN 120 MG SUPPLEMENTATION TO MENOPAUSAL SYMPTOMS AND QUALITY OF LIFE IN NON EQUOL PRODUCER WOMEN - R, Muharam; B, Budiman; IA, Rachman; RA, Nirmalasari (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: To investigate and compare symptom changes and quality of life (QOL) in non equol producer postmenopausal women after consuming daidzein supplementation. Methods: This was a single randomized clinical trial. It involved menopausal women. They were divided into two groups, one received placebo that contains calcium glycerophosphate 500 mg, vitamin D3 35 IU and daidzein group contain daidzein 120 mg, contain calcium glycerophosphate 500 mg, vitamin D3 140 IU for 8 weeks. Plasma equol was measured before supplementation. Menopause QOL (MenQOL) questionnaires have been utilized in the beginning and the end of treatment to assess the QOL. Results: A total of 41 women age 45-63 years old were included in this trial, 19 (47.5%) of them receive daidzein supplementation and others received control treatment. Menopausal symptoms decreased but not statistically significant compare to control group. Conclusion: About 8 weeks daidzein supplementation was not statistically improved MenQOL status in non equol producer postmenopausal women. Keywords: Menopause, Quality of life, Menopausal symptom, Isoflavone, Daidzein, Menopause quality of life.